An acellular assay to assess the genotoxicity of complex mixtures of organic pollutants bound on size segregated aerosol. Part I: DNA adducts - Topinka, Jan; Hovorka, Jan; Milcova, Alena; Schmuczerova, Jana; Krouzek, Jiri; Rossner, Pavel; Sram, Radim J (Toxicology letters, 2010)
An acellular assay consisting of calf thymus DNA with/without rat liver microsomal S9 fraction was used to study the genotoxicity of complex mixtures of organic air pollutants bound to size segregated aerosols by means of DNA adduct analysis. We compared the genotoxicity of the organic extracts (EOMs) from three size fractions of aerosol ranging from 0.17μm to 10μm that were collected by high volume cascade impactors in four localities of the Czech Republic differing in the extent of the environmental pollution: (1) small village in proximity of a strip mine, (2) highway, (3) city center of Prague and (4) background station. The total DNA adduct levels induced by 100μg/ml of EOMs were analyzed by (32)P-postlabelling analysis with a nuclease P1 method for adduct enrichment. The main finding of the study was most of the observed genotoxicity was connected with a fine particulate matter fraction (<1μm). The concentrations of carcinogenic polycyclic aromatic hydrocarbons (c-PAHs) in EOMs indicate that fine fractions (0.5-1μm) bound the highest amount of c-PAHs in all aerosol sampling sites, which might be related to the higher specific surface of this fraction as compared with a course fraction (1-10μm) and higher mass as compared with a condensational fraction (0.17-0.5μm). As for aerosol mass, both fine and condensational fractions are effective carriers of c-PAHs. Similarly, the DNA adduct levels per m(3) of air were highest for the fine fraction, while the condensational fraction (strip mine site and city center) revealed the highest DNA adduct levels in cases where aerosol mass is taken into consideration. A strong correlation was found between the c-PAHs and DNA adduct levels induced by EOMs in all the localities and for various size fractions (R(2)=0.98, p<0.001). It may be concluded that the analysis of total DNA adducts induced in an acellular assay with/without metabolic activation represents a relatively simple method to assess the genotoxic potential of various complex mixtures.
Keywords: Liver; Cattle; Animals; skot; DNA Damage; Mutagenicity Tests; aerosoly; játra; DNA; adukty DNA; Particulate Matter; testy genotoxicity; neparametrická statistika; Aerosols; poškození DNA; Air Pollutants; polycyklické aromatické uhlovodíky; DNA Adducts; Polycyclic Aromatic Hydrocarbons; krysa rodu Rattus; Statistics, Nonparametric; zvířata; látky znečišťující vzduch; Rats; pevné částice